EFIKASI DIRI DAN DUKUNGAN SOSIAL DOSEN PEMBIMBING SKRIPSI PADA PROKRASTINASI AKADEMIK MAHASISWA UNIVERSITAS UDAYANA - Wiranti, Ni Nyoman; Supriyadi, Supriyadi (Jurnal Psikologi Udayana; Vol 2 No 1 (2015), 2015)
Writing thesis is one of the important academic area as one of the requirements to earn a bachelor degree (Catrunada, 2008). In the process of writting thesis, a lot of student who have difficulties and failures are caused by the tendency of procrastination. Judging from internal factor, self-efficacy is one of the variables involved in the smoothness of university student's thesis. While from external factor, supervisor support is considered essential for the smoothness of university student's thesis (Ratnawati, 2007). This study aims to find the relationship between self-efficacy and supervisor social support toward academic procrastination.   Respondents in this study are a student at Udayana University as many as 98 students using simple random sampling as a sampling method. This study used content validity and reliability of Cronbach Alpha. Measured instruments used are the self-efficacy scale (18 items; rxx` = 0.780), supervisor social support scale (22 items; rxx` = 0.929) and academic procrastination scale (33 items; rxx` = 0.955).   Data processed by multiple linear regression analysis. The results show there is a relationship between self-efficacy and supervisor social support toward Udayana University student academic procrastination (r = 0.695, p = 0.000). The coefficient of determination obtained at 0.483, which means the effective contribution of variables self-efficacy and social support to academic procrastination were 48.3%.   Keywords: self-efficacy, social support, academic procrastination, university student